Are benzoylium and nitrilium ions produced from substituted 2‐arene‐2‐oxazolines during mass spectrometry? A study based on density functional theory calculations, quantum theory of atoms in molecules, and electrospray ionization tandem mass spectrometry. (27th December 2022) - da Silva Borges, Letícia; Batista, João Henrique Carvalho; Bozzini, Leandro; Lourenço, Celso Donizete; Lopes, Norberto Peporine; Clososki, Giuliano Cesar; Vessecchi, Ricardo
Abstract : Rationale: Oxazolines are important compounds for drug development, synthesis, and pharmaceutical applications. Interest in analyzing and developing methods to characterize reaction products from these small heterocyclics has led us to study the gas‐phase reactivity and fragmentation of seven 2‐arene‐2‐oxazolines compounds using computational chemistry combined with mass spectrometry. Method: Protonation sites were investigated using computed proton affinity, gas‐phase basicity, and some quantum chemistry descriptors of reactivity; the B3LYP/6–31+G(d, p) computational model was used. Fragmentation mechanisms were suggested by employing data from collision‐induced dissociation (CID), energy‐resolved plots from MS/MS spectra, multiple‐stage experiments, and survival‐yield method. Results: Protonation studies based on quantum theory of atoms in molecules (QTAIM) and computational thermochemistry were useful to describe the reactivity of the investigated 2‐arene‐2‐oxazolines, which can be protonated at the nitrogen atom. Three major fragmentation pathways were identified for the protonated molecules: formation of (a) benzoylium or (b) nitrilium ions through elimination of 71 and 72 u from the protonated molecules, respectively, and (c) elimination of 54 u from [M+H] + . These pathways were exploited by the density functional theory calculations combined with QTAIM studies. Conclusions: Our results can help in identifying 2‐arene‐2‐oxazoline derivatives using electrospray ionization tandem mass spectrometry (ESI‐MS/MS), which can be applied for monitoring reactions through the identified diagnostic ions (product ions). Also, we can suggest that benzoylium and nitrilium ions emerge during fragmentation under CID conditions.